AN AUDIT OF SEROLOGICAL TESTS CARRIED OUT AT CLINICAL LABORATORY OF AYUB TEACHING HOSPITAL, ABBOTTABAD - Ally, Sirajuddin Hassan; Ahmed, Ayesha; Hanif, Ruhila (Journal of Ayub Medical College Abbottabad, 2005)
Background: Clinical audit is an important tool for reviewing and improving the quality of service in clinical laboratories. Here we present an audit of total serology test requests and the frequency of positive tests out of these in a calendar year. Methods: This is an audit of serology tests carried out at Microbiology section of Clinical Laboratory of Ayub Teaching Hospital, Abbottabad. We counted all the serology test requests for the year 2004. These tests requests were grouped month wise. The frequency of positive tests out of the total test requests were calculated. The tests included Widal, Toxoplasma, Brucella, Anti DNA, Anti Nuclear factor (ANF), Rheumatoid Arthritis Factor (RAF), HIV, HBsAg, HCV, Intra Chromatographic Technique for tuberculosis (ICT-TB), Purified Protein Derivative (PPD), Venereal Disease Research Laboratory (VDRL) test, Anti-Streptolysin-O-test (ASOT) and pregnancy test. Results and Conclusions: This audit gives a clear idea of trends of test requests in our hospital. It reflects accuracy of clinicians' judgment in some tests and failure in others, prevalence of different diseases, seasonal variation in number of test requests for some tests and impact of awareness campaigns on attitude of clinicians towards certain diseases. This will help us in planning our laboratory requirements to improve quality. Keywords: Serology, Audit, Clinical laboratory